Examination Of Corporate Sustainability Disclosure Level And Its Impact On Financial Performance - Chiong, Paul Tiong Nyit (2010)
This research study seeks to determine the levels of disclosure of corporate sustainability reports published in 2008 that were prepared using these guidelines. Moreover, it examines whether there is a difference in disclosure levels between regions and industries. In addition, this study investigates the relationship between corporate sustainability disclosure level and financial performance, a study which did not yield a conclusive result in past studies.